The start of X-ray generator NESTOR comissioning - Androsov, V.; Bezdetko, O.; Boriskin, V.; Gladkikh, P.; Gokov, S.; Gordienko, A.; Grevtsev, V.; Gvozd, A.; Ivashchenko, V.; Kalamayko, A.; Karnaukhov, I.I.; Karnaukhov, I.M.; et al. (Вопросы атомной науки и техники, 2013)
The first results of the NESTOR facility commissioning are presented. 60 MeV electron linac injector has been tested and the first electron beam with project parameters was registered at the screen monitors. Electron beam was passed through the transportation channel and injection system. The beamh of electrons was observed and controlled in the screen monitors in the expected range.